Periodic Trends in Lanthanide Compounds through the Eyes of Multireference ab Initio Theory - Aravena, Daniel; Atanasov, Mihail; Neese, Frank (Inorganic chemistry, 2016)
Regularities among electronic configurations for common oxidation states in lanthanide complexes and the low involvement of f orbitals in bonding result in the appearance of several periodic trends along the lanthanide series. These trends can be observed on relatively different properties, such as bonding distances or ionization potentials. Well-known concepts like the lanthanide contraction, the double-double (tetrad) effect, and the similar chemistry along the lanthanide series stem from these regularities. Periodic trends on structural and spectroscopic properties are examined through complete active space self-consistent field (CASSCF) followed by second-order N-electron valence perturbation theory (NEVPT2) including both scalar relativistic and spin-orbit coupling effects. Energies and wave functions from electronic structure calculations are further analyzed in terms of ab initio ligand field theory (AILFT), which allows one to rigorously extract angular overlap model ligand field, Racah, and spin-orbit coupling parameters directly from high-level ab initio calculations. We investigated the elpasolite Cs2NaLn(III)Cl6 (Ln(III) = Ce-Nd, Sm-Eu, Tb-Yb) crystals because these compounds have been synthesized for most Ln(III) ions. Cs2NaLn(III)Cl6 elpasolites have been also thoroughly characterized with respect to their spectroscopic properties, providing an exceptionally vast and systematic experimental database allowing one to analyze the periodic trends across the lanthanide series. Particular attention was devoted to the apparent discrepancy in metal-ligand covalency trends between theory and spectroscopy described in the literature. Consistent with earlier studies, natural population analysis indicates an increase in covalency along the series, while a decrease in both the nephelauxetic (Racah) and relativistic nephelauxetic (spin-orbit coupling) reduction with increasing atomic number is calculated. These apparently conflicting results are discussed on the basis of AILFT parameters. The AILFT derived parameters faithfully reproduce the underlying multireference electronic structure calculations. The remaining discrepancies with respect to experimentally derived data are mostly due to underestimation of the ligand field splittings, while the dynamic correlation and nephelauxetic effects appears to be adequately covered by CASSCF/NEVPT2.